Experimental Investigation on Vegetative Oils under Accelerated Thermal Ageing against Their Dielectric Strength - Siti Sufiah, Abd Wahid; Mohd Fikri Hilmi, Mohd Taib; Yanuar, Z. Arief; Mohd Hafizi, Ahmad; Noor Azlinda, Ahmad; Nor Asiah, Muhamad; Zuraimy, Adzis; Mohd Hafiez, Izzwan Saad (Institute of Advanced Engineering and Science., 2017)
Insulation is one of the most important parts in high voltage apparatus such as power transformer. Most power transformer use liquid insulation material, known as power transformer oil. Petroleum-based oil so called mineral oil has been used for many years as power transformer oil. This is due to its high dielectric field strength, low dielectric loses and good long-term performance. This research work has been carried out to investigate the effect of thermal accelerated ageing on electrical properties for several vegetative-based oils. The oil samples that have been used in this research work are soy bean-based oil (FR3) and commercial palm-based oil (PFAE). As comparison, Hyrax mineral oil has also been investigated. The results revealed that vegetative-based oils have as well as dielectric strength compared with mineral oil. It was found that the dielectric strength for all oil samples decreased when undergo the thermal accelerated ageing process.